On a Robust Descriptor of the Flue Organ Pipe Transient - HRUŠKA, Viktor; DLASK, Pavel (Archives of Acoustics, 2020)
The initial transient of an organ pipe is known to be of great influence to the perceived sound quality. At the same time, the unsteady process of the tone onset is essentially nonlinear and lacks exact repeatability, so the search for a robust descriptor is in place. Initial transients were recorded using an adjustable flue organ pipe. The blowing pressure and cut-up height were varied. Prony’s method was employed to analyze the results. Utilizing the Principal Component Analysis (PCA) on the standardized exponential model coefficients, it was shown that the transients are well described by just one scalar parameter. Its value is predominantly dependent on the number of important Prony’s components taking part in the transient process (i.e., the overall complexity of the transient signal). A strong correlation was found between the PCA component and the Strouhal number inverse.